Modern approaches and diagnostic tools in neurosurgical practice: a case of patient with intracranial hypotension and secondary cervical spine degeneration - A. L. Krivoshapkin; I. D. Savitskiy; A. S. Gaytan; I. A. Krotenkova; G. S. Sergeev; O. A. Abdullaev; E. Chesnulis (Сибирский научный медицинский журнал)
We report a case of a 47-years old woman presented to our department with the diagnosis of Chiari I malformation and extensive hydrosyringomyelia. Her main complains were severe headache and chronic pain syndrome in the left side of her breast and left arm. Magnetic resonance imaging (MRI) showed alterations suggestive of the presence of intracranial hypotension (IH), that was confirmed by measurement of cerebrospinal fluid (CSF) opening pressure and then CSF venous fistula was detected by computed tomography myelography (CTM). She was successfully surgically treated which leaded to the regression of the clinical symptoms and radiological alterations. Nevertheless, during her recovery after surgery she had an episode of recurrent left arm pain, which was interpreted as secondary cervical spine degeneration consequence. MRI confirmed C5-C6 disc herniation and transforaminal epidural injection of local anesthetic and corticosteroid solutions was performed. A week later she already felt significant improvement as her pain syndrome regressed a lot. IH should be considered in the differential diagnosis of headache and sagging brainstem and tonsils with cord syrinx on MRI and should not be misinterpreted as Chiari malformation. At the same time, transforaminal epidural injection appears to be an effective tool in modern neurosurgical practice allowing to determine the reason and accurate radiculopathy level.